Chlorogenic acid improves glucose tolerance, lipid metabolism, inflammation and microbiota composition in diabetic db/db mice - Yan, Yongwang; Li, Qing; Shen, Ling; Guo, Kangxiao; Zhou, Xu (Frontiers in Endocrinology, 2022)
Either chronic or acute administration with chlorogenic acid (CGA) improved glucose tolerance and insulin sensitivity. However, whether acute administration of CGA has beneficial effects on hepatic lipid metabolism and cecal microbiota composition remains to be explored. Consequently, in the current study, diabetic db/db mice were either administrated with CGA or metformin and db/m mice were used as control, to explore the effects of CGA on hepatic lipid metabolism including fatty acid oxidation and transportation, and triglyceride lipolysis and synthesis. Moreover, alterations of inflammatory response, anti-oxidative stress in liver and gut microbe composition were evaluated. The results showed that CGA administration decreased body weight and improved glucose intolerance and insulin resistance, and these effects were similar to metformin. CGA administration decreased hepatic lipid content by increasing gene expression of CPT1a, ACOX1, ATGL and HSL, and deceasing gene expression of MGAT1, DGAT1, DGAT2, CD36 and FATP4. CGA administration also restored the expression of inflammatory genes including TNF-α, IL-10, IL-6, IL-1β and genes encoding antioxidant enzymes including SOD1, SOD2 and GPX1. Notably, CGA administration improved bacterial alpha and beta diversity in the cecum. Moreover, CGA administration recovered the level of phylum Bacteroidetes and the abundance of genera majorly including Lactobacillus, Blautia and Enterococcus. In conclusion, CGA administration could improve symptoms of diabetes and microbes may critically mediate these beneficial effects.